Aquatic hyphomycetes as survivors and/or first colonizers after a red sludge disaster in the Torna stream, Hungary. Issue 4 (23rd July 2013) - Vass, Máté; Révay, Ágnes; Kucserka, Tamás; Hubai, Katalin; Üveges, Viktória; Kovács, Kata; Padisák, Judit
Abstract A dam of a red sludge reservoir had ruptured on October 4, 2010 in Hungary and a mixture of 1 million m3 red sludge and water inundated two villages via the Torna stream. The industrial waste wiped out all detectable forms of life in the Torna stream, mainly due to its high pH value (pH 12.8). To study the fungal colonization leaves, Fagus sylvatica, Quercus cerris, Populus nigra, and Salix alba leaf litter were used as baits at two sites of the Torna stream. The leaves were sampled at seven occasions between February and June 2011 and a total of 26 aquatic hyphomycetes were revealed. Tricladium sp., Heliscus lugdunensis, and Tetracladium marchalianum were the dominant species at the impacted site. The total number of fungal species was lower at the impacted than at the reference site. The peak number of species associated with leaf litter was achieved later at the impacted site. Fungal species richness between leaf‐species at the two sites was compared by Fisher's exact test. Gypsum, which was dispersed into the stream in order to reduce the alkalinity, formed a layer on the leaves. Its effect for fungal colonization is discussed.